The micro-level dynamics of regional productivity growth: The source of divergence in Finland - Petri Böckerman; Mika Maliranta (The Research Institute of the Finnish Economy (ETLA), 2003)
Productivity growth of the Finnish regions in 13 manufacturing industries is decomposed into micro-level sources by using plant-level data from 1975 to 1999. There are substantial regional differences in the intensity of productivity-enhancing restructuring. Dynamic competition is more intensive in Southern Finland, where the productivity level is also high. In contrast, plants located in Eastern Finland are equipped with lowproductivity technologies owing to persistently sluggish micro-level dynamics. Productivity dispersion between plants within industries is greatest in Southern Finland. We argue that intensive experimentation is a more reasonable interpretation of this finding than large static X-inefficiency in this high productivity region. – productivity ; competition ; efficiency ; micro-level restructuring ; regional disparities – – Suomen alueiden tuottavuuskasvu 13 teollisuusalalla vuosina 1975–1999 on hajotettu toimipaikkatason aineistoja käyttäen mikrotason lähteisiin. Tuottavuutta vahvistavan rakennemuutoksen intensiteetti vaihtelee alueiden välillä merkittävästi. Dynaaminen kilpailu on intensiivisintä Etelä-Suomessa, jossa tuottavuuden taso on myös korkea. Itäisen Suomen toimipaikoilla sen sijaan käytetään alhaisen tuottavuuden teknologioita, mikä johtuu pitkään jähmeänä pysyneestä mikrotason dynamiikasta. Toimipaikkojen välinen tuottavuushajonta on suurinta Etelä-Suomessa. Argumentoimme, että tällä korkean tuottavuuden alueella esiintyvä intensiivinen kokeileminen selittää paremmin tämän havainnon kuin se, että X-tehottomuus olisi siellä suurta. – tuottavuus ; kilpailu ; tehokkuus ; mikrotason rakennemuutos ; alue-erot
Keywords: O12; R23; 330; Produktivität; Wettbewerb; Wirtschaftliche Effizienz; Regionale Disparität; Finnland